Realisasi Anggaran Pendapatan dan Belanja (APB) Desa (Studi Kasus Desa Hilir Kecamatan Tambelan) - Sari, Riska Putri; Zahrah, Alia; Humairoh, Tisya (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to analyze strategies for increasing local revenue and managing village resources in Hilir Village, Tambelan District, Bintan Province.Regional revenue is an important indicator to assess regional independence, and village funds are an important instrument to finance development at the village level.The research method used is a literature review by collecting theoretical references on the topic being discussed.The results show that Hilir Village has potential in the development of the fisheries sector and fisheries trade. The 2023 Village Budget Implementation Report (APB Desa) records village revenues and expenditures in detail and shows that fiscal surpluses indicate good financial management capabilities. However, village expenditures tend to exceed revenues, especially in several areas such as village administration and implementation of village development. Recommendations for strategies to increase local revenue and village resource management include increasing the efficiency and transparency of village financial management, increasing the potential for sectoral revenues such as the fisheries sector, including optimizing the use of information technology in management and public services. In addition, the allocation of village resources needs to be evaluated in detail to ensure effective and sustainable utilization. In summary, efforts to increase local revenue and sustainably manage village resources are important steps towards self-reliance and sustainable development at the village level. With the right strategies, it is expected that Hilir Village and its neighboring regions can achieve sustainable economic growth and improve the overall welfare of the community.